Formulasi Yoghurt Sinbiotik dengan Inkorporasi Pati Uwi Ungu Termodifikasi: Evaluasi Sineresis, Viabilitas Bakteri Probiotik, dan Daya Terima Organoleptik - Pangaribuan , Apriliyani Putri; Saputri , Muharni; Tambunan , Ika Julianti; Muzakkir, Muzakkir; Sembiring , Fanny Rizki; Indriana , Meutia; Salman, Salman (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Yogurt quality improvement can be achieved through synbiotic formulations combining probiotic bacteria (Lactobacillus bulgaricus, Streptococcus thermophilus, Lactobacillus rhamnosus) with prebiotics from modified purple yam starch (Dioscorea alata). This plant contains 7.54% inulin and has potential as a natural stabilizer, but its utilization in synbiotic yogurt remains suboptimal. This study aims to evaluate the effect of modified starch incorporation on probiotic viability, physical stability, and sensory acceptance. Objective: This research aimed to examine the capability of modified purple yam starch as a prebiotic source in synbiotic yogurt, focusing on its impact on syneresis, bacterial viability, and organoleptic properties. Methods: An experimental study using a Completely Randomized Design (CRD) with six treatments. The process included purple yam starch extraction, starch modification via autoclaving (110°C and 121°C), yogurt fermentation using three bacterial strains, and evaluation of pH, syneresis, Total Plate Count (TPC), and hedonic tests by 20 panelists. Data analysis involved descriptive statistics, Mann-Whitney, and Spearman correlation tests. Results: Yogurt formulations with modified yam starch yielded optimal pH (6.81 with L. rhamnosus) and highest syneresis (30.02%). Bacterial viability reached 431 × 10³ CFU/mL (10⁻² dilution) for L. rhamnosus. Organoleptic tests showed the highest scores for aroma (6.90 ± 0.31) and a significant correlation between taste-thickness (ρ=0.52; p<0.05). Color was consistent (score 6), while texture preference varied (scores 5-7). Conclusion: Modified purple yam starch effectively functions as a prebiotic and stabilizer in synbiotic yogurt, supporting probiotic viability and sensory acceptance. This formulation holds promise as a functional food product utilizing local ingredients.